Experiences gained from introduction of silver carp in Gobindsagar reservoir (Himachal Pradesh) for reservoir fisheries development in India - Kaushal, D K (The Indian Journal of Animal Sciences, 2007)
The exotic fish from China, Hypophthalmicthys molitrix, the silver carp is being stocked in reservoirs, ponds andtanks throughout India but nowhere else it bred naturally excepting Gobindsagar reservoir (Himachal Pradesh). Thisreservoir (11,300 ha) was formed in 1962 across the river Sutlej and till mid 1965 the reservoir had dominance of itsindigenous fishery of Labeo dero and Torputitora. The reservoir fishery was altered with its stocking by three carps (C.catla, L. rohita and C. mrigala) in 1962 to result in their dominance till 1977-78. In 1971 few specimens of silver carpand grass carp, were washed down to the reservoir due to breach of Deoli Fish Farm. This accidental entry of silver carpto the reservoir led to formation of its naturalized stock, contributing to the reservoir fishery. Accordingly, the fish catchof the reservoir progressively increased from 0.06 t (1977-78) to 1023.5 t (2052-03) with predominance of silver carp(85.1%). The factors like inflowing coldwater of the river Beas to river Sutlej, abundance of phytoplankton (Ceratirum)in the reservoir, availability of breeding grounds and high fecundity of fish were found to favourable for establishmentof silver carp fishery.Though the outstanding fishery of silver carp, in Gobindsagar reservoir, earning good revenue is a glaring exampleof increasing fish production from a reservoir, the gains achieved when weighted against the social, economic andecological consequences, the introduction of silver carp in any other reservoir of India needs to be given a secondthought because of its two negative impacts. Firstly, after its introduction, the developing of major carp fishery ofC.catla and L.rohita and also the ingenious fishery of T.putitora and L.dero of the reservoir were adversely affected.Secondly, the shelf life of silver carp was of shorter duration due to which its palatability was not accepted by theconsumers reducing its market value